2016
DOI: 10.3847/0004-637x/830/2/122
|View full text |Cite
|
Sign up to set email alerts
|

Timing Observations of PSR J1023+0038 During a Low-Mass X-Ray Binary State

Abstract: Transitional millisecond pulsars (tMSPs) switch, on roughly multi-year timescales, between rotation-powered radio millisecond pulsar (RMSP) and accretion-powered low-mass X-ray binary (LMXB) states. The tMSPs have raised several questions related to the nature of accretion flow in their LMXB state and the mechanism that causes the state switch. The discovery of coherent X-ray pulsations from PSRJ1023+0038 (while in the LMXB state) provides us withthe first opportunity to perform timing observationsand to co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
146
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(170 citation statements)
references
References 82 publications
22
146
2
Order By: Relevance
“…X-ray pulsation searches in the redback transitional millisecond pulsar PSRJ1023+0038 (e.g., Archibald et al 2015;Jaodand et al 2016) have established that one can successfully account for such nondeterministic orbital variations by searching over a small deviation in the time of ascending node (T asc ). Therefore, when folding the GBT radio data with X-rayderived ephemerides, we searched both over DM and a ΔT asc value compared to the fiducial ephemeris value.…”
Section: Direct-folding Search With X-ray-derived Ephemerismentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray pulsation searches in the redback transitional millisecond pulsar PSRJ1023+0038 (e.g., Archibald et al 2015;Jaodand et al 2016) have established that one can successfully account for such nondeterministic orbital variations by searching over a small deviation in the time of ascending node (T asc ). Therefore, when folding the GBT radio data with X-rayderived ephemerides, we searched both over DM and a ΔT asc value compared to the fiducial ephemeris value.…”
Section: Direct-folding Search With X-ray-derived Ephemerismentioning
confidence: 99%
“…However, there is at least one situation where, besides the short-term fluctuations discussed above, there is also a decadelong (secular?) variation of the orbit thatcorresponds to an overall shrinkage of the binary orbital separation (see, e.g., PSR J1023+0038; Jaodand et al 2016). …”
Section: Bws and Redbacksmentioning
confidence: 99%
“…The more recent discovery of transitional millisecond pulsars (tMSPs), which transition back and forth between a rotationpowered MSP and an accretion-powered low-mass X-ray binary (LMXB) state (Archibald et al 2009;Papitto et al 2013;Bassa et al 2014), confirmed the basic recycling model of Alpar et al (1982) and Radhakrishnan & Srinivasan (1982) in which a neutron star is spun up to millisecond spin periods due to the accretion of matter and angular momentum. At the same time, the tMSPs have also raised many questions about the detailed physics of the pulsar recycling process and how efficient it can ultimately be in terms of spinning up neutron stars (e.g., Archibald et al 2015;Deller et al 2015;Papitto et al 2015;Jaodand et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While radio pulsations have only been detected from tM-SPs in rotation-powered states, optical and X-ray pulsations have been detected from PSR J1023+0038 in its accreting state (Archibald et al 2015;Jaodand et al 2016;Ambrosino et al 2017;Zampieri et al 2019). Additionally, while γray pulsations have been detected from a large number of nearby MSPs, it remains an open question as to whether or not γ-ray pulsations from a tMSP are also suppressed during accreting states.…”
Section: Pulsation Detection Feasibilitymentioning
confidence: 99%